2019
DOI: 10.1088/1742-6596/1378/2/022060
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Effects of Fused Deposition Modelling on the Mechanical Properties of Polylactide Composites: A Review

Abstract: Polymers are generally inferior in mechanical properties to metals which are the current orthopaedic material for osseointegration in many parts of the world today. This assertion also applies to poly(lactic acid) (PLA), a polyester that has been recently found applicable in tissue remodelling. To improve on its mechanical properties, several processing techniques, inclusive of fused deposition modelling (FDM) also branded as fused filament fabrication (FFF), have been used. FDM has been endeared to many resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…7 shows the effect of infill density on the compressive strain and deformation value. The result from this simulation study agrees with the finding in the previous experimental result where the percentage of infill provides a significant impact on the compressive properties [14]. It was concluded that a higher infill percentage provides higher compressive strength for the printed parts.…”
Section: Table 4 -Analysis Of Variancesupporting
confidence: 91%
“…7 shows the effect of infill density on the compressive strain and deformation value. The result from this simulation study agrees with the finding in the previous experimental result where the percentage of infill provides a significant impact on the compressive properties [14]. It was concluded that a higher infill percentage provides higher compressive strength for the printed parts.…”
Section: Table 4 -Analysis Of Variancesupporting
confidence: 91%
“…They continued to study on the infill percentage on toughness and found that the increase in infill from 75% to 100% resulted in a two-fold toughness improvement, but the improvement is insignificant when the shift from 50% to 70% infill [66]. However, the high amount of infill requires a high amount of material and time to complete the part, causing high manufacturing cost [23,67]. In contrast, low %infill benefits the part accuracy.…”
Section: Infill Volume (%Infill)mentioning
confidence: 99%
“…time to complete the part, causing high manufacturing cost [23,67]. In contrast, low %infill benefits the part accuracy.…”
Section: Nozzle Geometrymentioning
confidence: 99%
“…The thermoplastic materials are melted in a hot liquefier before being extruded through a nozzle to form the different shapes. In order to extrude, thermoplastic filaments must be in a semi‐solid state 11,24,35 . The movement of the nozzle in an X – Y plane deposits semi‐solid filaments on the layer below, which then solidify, integrate, and cool.…”
Section: Introductionmentioning
confidence: 99%